2019
DOI: 10.1016/j.jclepro.2018.12.287
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the role of triple helix system intermediaries in nurturing an industrial biotechnology innovation network

Abstract: The rate of transition to a circular economy would largely be influenced by how successfully sustainable niche innovation can be developed and adopted. This paper measures and evaluates the effectiveness of employing a triple helix-based system intermediary as a policy tool for nurturing a niche innovation network in line with circular economy transition. This was achieved through a complete social network analysis of a national industrial biotechnology innovation network, in which the organisation functioning… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
41
0
7

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(48 citation statements)
references
References 54 publications
0
41
0
7
Order By: Relevance
“…[100] (p. 349) When applying social network theory in the context of innovation, it has been suggested that stimulating innovation within networks requires a combination of both strong and weak ties [101][102][103]. "Weak ties aid exploration (the generation of new ideas), whereas strong ties aid exploitation (the implementation of new ideas)" [35] (p. 212). The creation and diffusion of innovation are mostly attributed to weak ties [104].…”
Section: Social Network Theorymentioning
confidence: 99%
See 1 more Smart Citation
“…[100] (p. 349) When applying social network theory in the context of innovation, it has been suggested that stimulating innovation within networks requires a combination of both strong and weak ties [101][102][103]. "Weak ties aid exploration (the generation of new ideas), whereas strong ties aid exploitation (the implementation of new ideas)" [35] (p. 212). The creation and diffusion of innovation are mostly attributed to weak ties [104].…”
Section: Social Network Theorymentioning
confidence: 99%
“…Second, when matching collaborators, human decisions are often subject to the "homophily principle"-a tendency in which people form ties with similar others [33]. Selecting a "friend of a friend" helps strengthen existing social clusters [33], but does not help to reach those unknown communities and individuals [34], who could potentially contribute to innovation [35]. Third, although one may notice the limitation of professional social matching based on human decisions, it is difficult to find suitable tools and data to resolve the problem [34].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, constructing an innovation diffusion mechanism also requires a lot of resources. ITI is also impacted by economic structures [ 18 ], industrial transfer [ 19 ], political relationships [ 20 ], and market demand or other aspects [ 21 ], and the combination of all these factors means that ITI systems are inherently complex.…”
Section: Introductionmentioning
confidence: 99%
“…Within companies, environmental sustainability focuses at first on the prevention of pollution and then on the responsible management of resources in the production process, in order to reach the desirable stage of sustainable environmental development, in which the purpose of environmental care is fully and strongly rooted in the company's corporate and competitive strategy [55]. This transition requires a change from the current concept of economy to the concept of circular economy [56], understood as one that is "restorative and regenerative by design and aims to keep products, components, and materials at their highest utility and value at all times" ([57], p. 2). This change in the economic paradigm faces resistance, not only from companies, but also from the markets and other economic actors, although the latter may also be part of the solution, when they all share the same vision of sustainability [58][59][60].…”
Section: Triple Helix and Environmental Sustainabilitymentioning
confidence: 99%